Learning Zulu : A Secret History of Language in South Africa - Sanders, Mark, 1968- (Book collections on Project MUSE., 2016)
"Why are you learning Zulu?" When Mark Sanders began studying the language, he was often asked this question. In Learning Zulu, Sanders places his own endeavors within a wider context to uncover how, in the past 150 years of South African history, Zulu became a battleground for issues of property, possession, and deprivation. Sanders combines elements of analysis and memoir to explore a complex cultural history. Perceiving that colonial learners of Zulu saw themselves as repairing harm done to Africans by Europeans, Sanders reveals deeper motives at work in the development of Zulu-language learning--from the emergence of the pidgin Fanagalo among missionaries and traders in the nineteenth century to widespread efforts, in the twentieth and twenty-first centuries, to teach a correct form of Zulu. Sanders looks at the white appropriation of Zulu language, music, and dance in South African culture, and at the association of Zulu with a martial masculinity. In exploring how Zulu has come to represent what is most properly and powerfully African, Sanders examines differences in English- and Zulu-language press coverage of an important trial, as well as the role of linguistic purism in xenophobic violence in South Africa. Through one person's efforts to learn the Zulu language, Learning Zulu explores how a language's history and politics influence all individuals in a multilingual society.